2021
DOI: 10.3389/fpls.2021.661909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Amendment With Wood Ash on Transpiration, Growth, and Metal Uptake in Two Contrasting Maize (Zea mays L.) Hybrids to Drought Tolerance

Abstract: Wood ash as a soil amendment has gained wide spread acceptance in the recent years as a sustainable alternative to chemical fertilizers, although information regarding the effects of its application on maize growth and yield in the context of climate change and increasing drought severity is lacking till date. In the present study, field and pot trials were carried out at the experimental farm of the University of Padova at Legnaro (NE Italy) in a silty-loam soil in order to investigate the effects of soil ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Choice of biomass ashes as appropriate raw material: Biomass ashes are the primary waste material generated during the energy (heat and power) production at cogeneration plants (Masto et al, 2015). Biomass ashes (fly and bottom ashes), if securely and adequately applied into the soil, may play a significant role in plant nutrition and soil improvement as well as nutrient cycling favorable for agriculture, gardening, and greenery landscaping purposes (Anggarani et al, 2021;Bhattacharya and Chattopadhyay, 2002;Jain et al, 20212;Romdhane et al, 2021). The composition of wood ashes incorporates a mixture of chemical elements mainly in the form of oxides, hydroxides, carbonates, and silicates (Demeyer et al, 2001).…”
Section: Case Example In Elaboration Of Peat-free Soil Amendmentmentioning
confidence: 99%
“…Choice of biomass ashes as appropriate raw material: Biomass ashes are the primary waste material generated during the energy (heat and power) production at cogeneration plants (Masto et al, 2015). Biomass ashes (fly and bottom ashes), if securely and adequately applied into the soil, may play a significant role in plant nutrition and soil improvement as well as nutrient cycling favorable for agriculture, gardening, and greenery landscaping purposes (Anggarani et al, 2021;Bhattacharya and Chattopadhyay, 2002;Jain et al, 20212;Romdhane et al, 2021). The composition of wood ashes incorporates a mixture of chemical elements mainly in the form of oxides, hydroxides, carbonates, and silicates (Demeyer et al, 2001).…”
Section: Case Example In Elaboration Of Peat-free Soil Amendmentmentioning
confidence: 99%
“…21 Meanwhile, the study of the negative impacts brought by ash indicated that at high concentration, ash leads to the increase of pH, lack of nitrogen nutrients and high level of heavy metal cytotoxicity. 22 The present study is the first attempt to investigate the chemical components, morphology and size of the particles formed in ash produced from the burning of plants, and tests their effect on bean sprout germination, rooting, and leaf and stem growth. On the other hand, the present work aims to develop a nanozyme with PL activity and to test its effect on plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have emphasized the importance of the soil-borne microbiome in maintaining agricultural sustainability [ 15 , 16 ]. Studies on soil amendments generally select simple components [ 17 , 18 ]. However, there are few studies investigating the effects of exogenous composite soil amendments and cropping systems on soil rare and abundant sub-communities.…”
Section: Introductionmentioning
confidence: 99%